The Importance of Intellectual Capital in the Execution of Court Cases on the Example of Common Courts Subordinate to the Court of Appeal in Szczecin in Poland - Rafal MAZUR (Communications of International Proceedings, 2024)
The article analyses the functioning of a modern IT solution in budgetary units, and more specifically in common courts located in the West Pomeranian and Lubusz Voivodeships operating within the Szczecin Appellate Office in Poland. The focus was on the effects achieved after the implementation of an application for recording court receivables, made in three-tier technology, as well as the launch of a large print centre for all common courts in Poland. The analyzed solution, along with the necessary services, is installed at the Court of Appeals in Szczecin and is connected to a number of external applications, such as the Integrated Accounting and Personnel System (ZSRK), the Central Printing System, the Economic Information Offices, the Postal Service System for Return Receipt and Electronic Acknowledgement of Receipt, the Reporting Integrator of the Ministry of Justice and the departmental case law systems in each court. This article uses the following methods: observation, documentary analysis and interview of selected employees of 27 courts in the Szczecin appellate court. The research results confirm the great significance of human resources and IT solutions for the efficient functioning of justice units.
Keywords: innovation; development; common judiciary